Transforming citywide sanitation provision: Utility voices on pit emptying and transport services in Kenya and Zambia - Grisaffi, Claire; Oluoch, Priscillah; Hamuchenje, Eustakia M.; Phiri, Jessica; Salano, Gertrude; Hawkes, Lisa; Parker, Alison (Frontiers in Water, 2022)
This paper documents the key challenges faced by utilities in sub-Saharan Africa attempting to establish citywide safe manual and semi-mechanized latrine pit emptying, transport and disposal services. The research aims to take a snapshot of utilities at a pivotal point in service development, where initial services have been piloted and the utilities are looking to go to scale. We use the CWIS framework to guide analysis of perspectives of the implementing agencies in Livingstone, Zambia, and Malindi, Kenya, using a secondary data review and 34 key informant interviews. This paper confirms previous findings around the high cost of safe sanitation services in low-income areas, the barriers of emptiability, the engagement of manual pit emptiers and the requirement for investment in supporting systems. Areas for future research were identified, including approaches for service delivery to reduce the decision load on the household, structures of engagement and regulation of pit emptiers, and finally how regulation could support incremental improvements towards full coverage, including the lowest income households. The research documents, for the first time in the region, the challenges of dealing with disgust in establishing these new services and the conflicting role of public utilities as both commercial and social organizations. The current model for private sector delivery of the service is politically viable and reduces the risk and cost burden on the utilities. However, it is likely to leave the utilities unable to scale sanitation to low-income areas.